A Dialogue between Aquiles and Percy Jackson in Homero and Rick Riordan Epic Heroism Contemporary and Readings Reader Formation (Global Journal of Human-Social Science, 2019)
This paper intends from the dialogue with classic and postmodern literary readings, to present a proposal of poetic interpretation of the works The Iliad of Homer and The thief of rays, of Rick Riordan in addition to the Manichaeism Canon and Mass Literature. In this way, we intend to think the issue of literary criticism, from the characters Achilles and Percy Jackson, reflecting on the issues that the literary work can elicit in formation of readers.
Keywords: hero literature reading formation of readers